On the effect of alpha-admissibility and theta-contractivity to the existence of fixed points of multivalued mappings - Mınak, Gülhan; Altun, Ishak (Nonlinear Analysis: Modelling and Control, 2016)
In this study, we give some fixed point results for multivalued mappings using α-admissibility and θ-contractivity of multivalued mappings on complete metric spaces. Our results are proper generalizations of some fixed point results related to multivalued contraction. We also provide an example showing this fact. Finally, we obtain some ordered fixed point results for multivalued mappings as corollary.